1991
DOI: 10.1007/bf02285464
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling in nuclear medicine

Abstract: Modern imaging techniques can provide sequences of images giving signals proportional to the concentrations of tracers (by emission tomography), of X-ray-absorbing contrast materials (fast CT or perhaps NMR contrast), or of native chemical substances (NMR) in tissue regions at identifiable locations in 3D space. Methods for the analysis of the concentration-time curves with mathematical models describing the physiological processes and the appropriate anatomy are now available to give a quantitative portrayal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 47 publications
0
32
0
1
Order By: Relevance
“…It is virtually impossible to reach uniqueness in biological modelling, because one can almost always find an alternative or more detailed model as a result of the presence of noise or inexactness of fit (Kuikka et al 1991). In this study, although five models were entertained to simulate the kinetics of functional and collection-injured platelets, we showed that the increase in detail or complexity of the last two models did not give substantial additional information.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is virtually impossible to reach uniqueness in biological modelling, because one can almost always find an alternative or more detailed model as a result of the presence of noise or inexactness of fit (Kuikka et al 1991). In this study, although five models were entertained to simulate the kinetics of functional and collection-injured platelets, we showed that the increase in detail or complexity of the last two models did not give substantial additional information.…”
Section: Discussionmentioning
confidence: 88%
“…Graphs were, however, highly regarded throughout the fitting and optimisation procedure (Box and Hunter 1965). The computer program Simulation, Analysis and Modelling (SAAM) was used in this study (Kuikka et al 1991;Foster and Boston 1983). The parameters calculated during compartmental modelling are expressed as a mean and range (given in parentheses).…”
Section: Methodsmentioning
confidence: 99%
“…The area under the retention fase of the curve is proportional to the medium transit time. As considered for other organs (kidney and thyroid) it is assumed that the ratio between the initial height of the retention phase and the high of the vascular peak represents the (hepatic) extraction fraction at the first pass -HEF [11][12][13] .…”
Section: -Graphic Representation Of Function H (T)mentioning
confidence: 99%
“…[45][46]47 By writing out ( ) = in ( ) * ℎ ( ), (9) becomes NOT THE PUBLISHED VERSION; this is the author's final, peer-reviewed (12) where the flow-weighted impulse residue function ( ) represents ( ) that would be measured if the inlet concentration curve were an impulse. The complete distribution of capillary transit times ℎ ( ) can then be determined using numerical deconvolution [44].…”
mentioning
confidence: 99%